'Christians, out here?' Encountering Street-Pastors in the post-secular spaces of the UK's night-time economy. (February 2015) - Middleton, Jennie; Yarwood, Richard
This paper explores the concept of the post-secular city by examining the growing presence of Street-Pastors in the night-time economy of British cities. Street-Pastors are Christian volunteers who work to ensure the safety of people on a 'night out'. We contribute to work that has called for greater attention to be placed on the ways in which religious faith and ethics are performed to create liminal spaces of understanding in urban areas. Drawing upon in-depth ethnographic research conducted in a range of UK towns and cities, we consider this distinct form of faith-based patrolling in relation to the spatial processes and practices of urban-nightscapes. By exploring the geographies of Street-Pastors, we not only contribute to more nuanced accounts of 'drinking spaces' but provide an empirical engagement with the growing body of work on urban rhythms and encounters.